Developmental Variation in Amygdala Volumes: Modeling Differences across Time Age and Puberty - Russell, Justin D. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2020)
BACKGROUND: There is evidence that the amygdala undergoes extensive development. The exact nature of this change remains less clear with evidence suggesting linear, curvilinear, and null effects. The aim of this study is the identification of a normative reference of left and right amygdala development by parceling variance into separate effects of age and longitudinal growth. METHODS: Data come from the National Institutes of Health MRI Study of Normal Brain Development. Participants in this sample were 54% female and ranged in age from 5 to 18 years (mean = 11.37) at study entry. RESULTS: As predicted, the age at initial scan moderated the slope of both left and right amygdala volumes demonstrating that the nature of longitudinal growth varies across age (i.e., steeper slopes observed among those first scanned at an early age). Follow up analysis showed that the positive longitudinal growth slope becomes non-significant at 13.1 years of age for the left amygdala, and 14.5 years for the right, suggesting growth of the left amygdala ‘peaks’ earlier than the right. CONCLUSIONS: Findings suggest that rapid increases in volumes at early ages decline as youth enter adolescence and may turn to minor declines in volume during late adolescence or early adulthood.